Application of Periodic Economic MPC to a Grid-Connected Micro-Grid*. Issue 23 (2015) - Pereira, M.; Limon, D.; Alamo, T.; Valverde, L.
Abstract: This paper presents the application of economic predictive control to minimize the cost of operating a non-isolated micro-grid connected to an electric utility subject to a periodic internal demand. A function that describes the economic cost of operating the plant taking into account aspects such as electric market costs, degradation of the micro-grid and amortization costs is proposed. Based on this cost and considering the periodic nature of the plant, an economic predictive controller capable of adapting to sudden changes on the cost function while guaranteeing stability and recursive feasibility has been successfully tested using the LTI model of an experimental congurable test-bed located at the laboratories of the University of Seville.